DETERMINAN TINGKAT KEMISKINAN DI INDONESIA - Klarasanti, Anggraini; Bendesa, I Komang Gde (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.08.TAHUN.2024DO - 10.24843/EEB.2024.v13.i08.p12, 2024)
The aims of this study are, 1) to analyze simultaneously and partially the effect of life expectancy, average length of schooling, per capita expenditure, population, unemployment rate, and the Covid-19 pandemic on poverty levels in Indonesian Provinces. 2) to analyze differences in poverty rates, life expectancy, average length of schooling, per capita expenditure, population, and unemployment rates between Western Indonesia and Eastern Indonesia. The number of observations used in this study were 408 observations. The data used is secondary data. The research was tested using panel data regression analysis techniques with the selected estimation model, namely the fixed effect model. The results of this research analysis are, 1) simultaneously life expectancy, average length of schooling, per capita expenditure, population, unemployment rate, and the Covid-19 pandemic have a significant effect on the poverty rate. 2) Partially, life expectancy, per capita expenditure, and population have a negative and significant effect on the poverty rate, the average length of schooling and the unemployment rate have no effect on the poverty rate. 3) There are significant differences in poverty rates, life expectancy, average length of schooling, per capita expenditure, population, and unemployment rates between Western Indonesia and Eastern Indonesia.